The portability of social rights of the United Kingdom with the European Union: Facts, issues, and prospects. Issue 4 (December 2018) - Holzmann, Robert; Wels, Jacques
The portability of social benefits – such as the state pension, child allowances and unemployment benefits – for international migrants is regulated by social security agreements concluded between countries or at supra-national level, such as within the European Economic Area (EEA). Focusing on the United Kingdom, this article aims at capturing the main issues that have been recently raised by such agreements, with particular emphasis on the case of migration between the UK and Europe. The first part of the paper summarises the main consideration researchers and policy makers should bear in mind in looking at portability. Using data from the 2013 World Bank migration matrix, the second part of the paper compares the stock of British migrants residing abroad and the stock of foreigners living in the United Kingdom. The third part of the paper summarises the main issues that were raised in relation to the EEA multilateral agreement including the notion of residence, the state pension, family allowances, and the portability of health care benefits. The conclusions highlight the main concerns and options that lie ahead following the withdrawal of the UK from the European Union.